Evaluation of Old Corrugated Container (OCC) by Blending with Carboxymethyl Cellulose (CMC) and Amphoteric Polyacrylamide (aPAM) - Nur Izdihar Ahmad,; Nor Mazlana Main, (Research Progress in Mechanical and Manufacturing Engineering, 2024)
The aim of this study is to evaluate the change on the old corrugated container (OCC) paper when blending with carboxymethyl cellulose (CMC) and amphoteric polyacrylamide (aPAM) as the dry strength additives (DSA). In the study, the condition involve 100% of OCC with 5 different percentages of DSA which is 0.5%,1.0%, 1.5%, 2.0% and 2.5%. The experiment in preparing the paper and paper testing is based on the TAPPI and MS ISO standards. Based on the result of the study, dry strength additives improve the paper's mechanical properties. In the ANOVA analysis, a significant result can be observed from the tearing index, the value is getting increasing when addition percentage of DSA that can reach 7.46 m.N.m2/g for the 100% OCC pulp with 2.5% CMC and 13.39 m.N.m2/g for 100% OCC pulp with 2.5% aPAM. Meanwhile, in the busting index and tensile index, they are also increase in different percentage of DSA for the ANOVA analysis. In the busting index, the highest value recorded at 2.83 kPa.m2/g for 100% OCC pulp with 2.5% CMC and the value for 100% OCC pulp with 2.5% aPAM is 2.62 kPa.m2/g. For the tensile index, the highest values recorded at 1.20 N.m/g for 100% OCC pulp with 2.5% CMC. In the  morphology analysis, the increased DSA will improve structure for paper such as less pores and broken fiber on the paper surface. When comparing CMC and aPAM, aPAM at 2.5% provided the highest improvement in the tearing index, while CMC at 2.5% showed better results for the bursting and tensile indices. Therefore, the choice between CMC and aPAM depends on the specific mechanical property that needs enhancement, with aPAM being more effective for improving the tearing index and CMC being better for enhancing the bursting and tensile indices. In conclusion, the addition of DSA in the paper properties improves the structure and mechanical properties of the paper.